2012
DOI: 10.1371/journal.pone.0030406
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic State Determines Sensitivity to Cellular Stress in Huntington Disease: Normalization by Activation of PPARγ

Abstract: Impairments in mitochondria and transcription are important factors in the pathogenesis of Huntington disease (HD), a neurodegenerative disease caused by a polyglutamine expansion in the huntingtin protein. This study investigated the effect of different metabolic states and peroxisome proliferator-activated receptor γ (PPARγ) activation on sensitivity to cellular stressors such as H2O2 or thapsigargin in HD. Striatal precursor cells expressing wild type (STHdhQ7) or mutant huntingtin (STHdhQ111) were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 65 publications
3
21
0
Order By: Relevance
“…Our data suggest increasing cellular Mn burden results in a corresponding induction of ribulose 5-phosphate, an effect that was exaggerated in HD striatal cells relative to control. This finding corroborates previous studies that demonstrate HD striatal cell impairments in mitochondrial dynamics and energetics 51, 52 . The genotype-dependent difference was apparent only at the cytotoxic 125µM Mn exposure, while increasing cellular Mn burden from vehicle to 31µM does not significantly increase ribulose 5-phosphate levels.…”
Section: Discussionsupporting
confidence: 93%
“…Our data suggest increasing cellular Mn burden results in a corresponding induction of ribulose 5-phosphate, an effect that was exaggerated in HD striatal cells relative to control. This finding corroborates previous studies that demonstrate HD striatal cell impairments in mitochondrial dynamics and energetics 51, 52 . The genotype-dependent difference was apparent only at the cytotoxic 125µM Mn exposure, while increasing cellular Mn burden from vehicle to 31µM does not significantly increase ribulose 5-phosphate levels.…”
Section: Discussionsupporting
confidence: 93%
“…Napolitano and colleagues (2011) demonstrated that pioglitazone has useful effects on mitochondrial dysfunction by interfering with the NF-κB signaling cascade, which is involved in the 3 nitropropionic acid model of HD in primary striatal cells [42]. Another study described that the metabolic condition determines sensitivity to cellular stress in HD, demonstrating that STHdh Q111 cells exhibited higher superoxide and ROS, an effect that was distinctly reduced by constitutively active PPARγ with rosiglitazone [43]. We previously reported that PPARγ played a major function in the pathogenesis of HD, and demonstrated that TZD and rosiglitazone modulated energy deficiency in the striatum of R6/2 mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also implicate PPARγ activation for the neuroprotective effects of rosiglitazone and pioglitazone in HD [22,[41][42][43]. Importantly, PPARγ mediated increases in anti-apoptotic Bcl-2 protein expression in PC12 cells protects against apoptosis [76].…”
Section: Discussionmentioning
confidence: 99%
“…In striatal cells in culture expressing mutant huntingtin STHdh(Q111), rosiglitazone increased mitochondrial biogenesis and protected against calcium dependent (thapsigargin-induced) mitochondrial dysfunction [128]. Similarly, in cultured rat primary cortical neurons expressing mutant huntingtin STHdh(Q111), PPARγ activation by rosiglitazone significantly attenuated thapsigargin-induced cell death, concomitant with reduced caspase activation, a delay in the loss of ΔΨ m , and a reduction of ROS generation [80]. In addition, a reduction in mitochondrial mass associated with the expression of mutant huntingtin in N2A cells, was rescued by rosiglitazone [29].…”
Section: Mechanisms Of Protection By Pparγ In Neurodegenerative Diseasesmentioning
confidence: 97%